Cardiomyocyte calcium handling in health and disease: Insights from in vitro and in silico studies - Sutanto, Henry; Lyon, Aurore; Lumens, Joost; Schotten, Ulrich; Dobrev, Dobromir; Heijman, Jordi (Progress in biophysics and molecular biology, 2020)
Calcium (Ca2+) plays a central role in cardiomyocyte excitation-contraction coupling. To ensure an optimal electrical impulse propagation and cardiac contraction, Ca2+ levels are regulated by a variety of Ca2+-handling proteins. In turn, Ca2+ modulates numerous electrophysiological processes. Accordingly, Ca2+-handling abnormalities can promote cardiac arrhythmias via various mechanisms, including the promotion of afterdepolarizations, ion-channel modulation and structural remodeling. In the last 30 years, significant improvements have been made in the computational modeling of cardiomyocyte Ca2+ handling under physiological and pathological conditions. However, numerous questions involving the Ca2+-dependent regulation of different macromolecular complexes, cross-talk between Ca2+-dependent regulatory pathways operating over a wide range of time scales, and bidirectional interactions between electrophysiology and mechanics remain to be addressed by in vitro and in silico studies. A better understanding of disease-specific Ca2+-dependent proarrhythmic mechanisms may facilitate the development of improved therapeutic strategies. In this review, we describe the fundamental mechanisms of cardiomyocyte Ca2+ handling in health and disease, and provide an overview of currently available computational models for cardiomyocyte Ca2+ handling. Finally, we discuss important uncertainties and open questions about cardiomyocyte Ca2+ handling and highlight how synergy between in vitro and in silico studies may help to answer several of these issues. •Ca2+-handling abnormalities play important roles in cardiac arrhythmogenesis.•Computer models enable studies of cardiac electrophysiology in health and disease.•Cardiomyocyte models can investigate complex Ca2+-dependent signaling pathways.•Cardiomyocyte models provide insight in bidirectional electromechanical coupling.•Interactions between in silico and in vitro studies may improve data accuracy.